2021
DOI: 10.1186/s12864-021-07377-9
|View full text |Cite
|
Sign up to set email alerts
|

G-quadruplexes in H1N1 influenza genomes

Abstract: Background Influenza viruses are dangerous pathogens. Seventy-Seven genomes of recently emerged genotype 4 reassortant Eurasian avian-like H1N1 virus (G4-EA-H1N1) are currently available. We investigated the presence and variation of potential G-quadruplex forming sequences (PQS), which can serve as targets for antiviral treatment. Results PQS were identified in all 77 genomes. The total number of PQS in G4-EA-H1N1 genomes was 571. Interestingly, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 52 publications
2
17
0
Order By: Relevance
“…We found out that 12 PQS motifs are present in the few segments of the IAV genome. It should be noted that one sequence identified in our study, 12KW, was previously found also by Brázda et al [ 20 ], while other potential quadruplex-forming sequences selected by our research groups varied. A possible explanation for this observation is that we identified PQS from influenza A virus vRNA segments using QGRS mapper and G4RNA screener, while Brázda et al utilized in this purpose G4hunter Web tool.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…We found out that 12 PQS motifs are present in the few segments of the IAV genome. It should be noted that one sequence identified in our study, 12KW, was previously found also by Brázda et al [ 20 ], while other potential quadruplex-forming sequences selected by our research groups varied. A possible explanation for this observation is that we identified PQS from influenza A virus vRNA segments using QGRS mapper and G4RNA screener, while Brázda et al utilized in this purpose G4hunter Web tool.…”
Section: Discussionsupporting
confidence: 62%
“…More recently, some papers described bioinformatics analyses of viral genomes (including human coronaviruses, [ 49 , 50 ] and influenza virus, [ 20 ]) to determine the presence of G-rich regions. In 2020, Bartas et al conducted a systematic and comprehensive analyses to study the occurrence of PQS sites and inverted repeats (IRs) loci in genomes of all known Nidovirales [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations